Pancreatic cyst fluid glucose: a rapid on-site diagnostic test for mucinous cysts. (November 2022) - Zamir, Efrat; Zelnik Yovel, Dana; Scapa, Erez; Shnell, Mati; Bar, Nir; Bar Yishay, Iddo; Ziv-Baran, Tomer; Younis, Fadi; Phillips, Adam; Lubezky, Nir; Shibolet, Oren; Ben-Ami Shor, Dana
Background: Pancreatic cystic fluid (PCF) analysis is frequently used for cyst diagnosis with carcinoembryonic antigen (CEA) being the most accepted biomarker. Low glucose levels in PCF were previously suggested as a marker for mucinous cysts. A bed-side glucometer is a point-of care, immediate, simple, and cheap method which requires a small volume of PCF. Objectives: The aim of our study was to identify the optimal glucose cut-off level for identifying mucinous cysts, evaluate the diagnostic accuracy of glucose compared to CEA, and validate glucometry against reference laboratory biochemical analysis. Design: A single-center prospective cohort study. Methods: Consecutive patients aged 18 and older, who underwent pancreatic cyst evaluation, at the Tel Aviv Medical Center between 2016 and 2021 were analyzed. Cyst type was defined based on clinical, laboratory, and radiologic findings. Glucose was measured using laboratory biochemical analysis and two glucometers. Receiver operating characteristic analysis derived sensitivity, specificity, and accuracy were calculated and McNemar test was used to compare between methods. Results: One hundred and one PCF samples were evaluated. The areas under the receiver operating characteristics curve for identifying mucinous cysts using glucometer, glucose laboratory, and their combination were 0.88 ( p < 0.001), 0.92 ( p < 0.001), and 0.93 ( p < 0.001), respectively. A glucose level of 87 mg/dL was identified as the optimal laboratory glucose threshold value to detect mucinous cyst with a sensitivity of 90.9%, specificity of 83.3%, and accuracy of 89.3, higher in comparison to cyst fluid CEA. Furthermore, PCF glucose levels had the strongest association with mucinous cysts. Conclusion: Our findings suggest that PCF glucose level is more accurate than CEA for the diagnosis of mucinous cysts. Glucometry glucose level assessment demonstrated an excellent correlation with laboratory glucose measurements and may become a useful diagnostic test.